Classification of models and mechanisms of family policy in developed countries - Temirbayeva, D.M. (BUKETOV BUSINESS REVIEW, 2017)
The article examines the objects, principles and functions of family policy, various approaches to the implementation of family policy in different countries. The main measures of the family policy in the field of fertility are revealed, as is known to the basic and most widely used measures in practice, measures include direct reduction of the costs of the child's birth, care and upbringing. The model of the system of goals, target indicators and measures in the areas of family policy is drawn up and the modal characteristics of periodic payments for children in OECD countries are illustrated. The review of the world practice of applying the main measures of family policy on its two main sections is made: the demographic and social protection of the family. The presented family policy in different countries has passed its historical path of development and the countries of Europe, North America and Australia have the most developed. The main principles of differentiation of benefits are the level of income of the household, the region of residence, the number of children, the age of children, family status, etc. The analysis revealed that solving the problem of combining production interests with family life became one of the priorities of state policy in many countries where this was and remains a matter of equality between men and women, since it is women in any country in the world who bear the primary responsibility for the family And household.